Knowledge and perception of cereal farmers and extension agents on fungicide use in northern Ghana - Otoo, James; Musah, R.; Olita, Toto; Ireland, Kylie B.; Zerihun, Ayalsew (2024)
BACKGROUND: Agricultural pesticide use in sub-Saharan Africa has doubled over the past three decades, with a greater relative increase for fungicides. As pesticide inputs continue to rise, so does the potential for the development of resistance. Here, we report on a survey conducted to understand pesticide resistance awareness, pesticide-use knowledge and practices of growers and agricultural extension officers (AEOs) in the cereals growing-belt of northern Ghana, with emphasis on fungicides. The results may inform development of strategies for improving pesticide literacy including resistance awareness, extension services and crop protection outcomes. RESULTS: The survey revealed a low level of pesticide-use knowledge for AEOs and growers. This was more so for growers with low education, predominantly women. Education level (and indirectly gender) influenced perceived effectiveness of fungicides and levels of adoption of cultural and agrochemical best practices. Only 28% of growers and 11% of AEOs practiced crop and fungicide rotations, respectively. More than half (53%) of the respondents indicated that fungicides used in northern Ghana are not effective. CONCLUSION: Given the low level of pesticide literacy of AEOs and growers, training programs on best practice for the use of pesticides, with targeted initiatives for female growers, would improve crop protection outcomes and safety. The limited adoptions of crop rotation and repeated use of fungicides with the same active ingredients, along with >50% of respondents reporting ‘fungicides not working’ suggest the potential presence of fungicide resistance cases in growers' fields in the Northern region of Ghana. Further work is needed to determine the incidence of resistance in the region. It is recommended that a key policy priority should focus on understanding broader agrochemical-use practices, crop losses and household-level food security in the presence of resistance risks. © 2024 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.